2020
DOI: 10.1108/afr-05-2020-0068
|View full text |Cite
|
Sign up to set email alerts
|

The ripple effect of credit accessibility on the technical efficiency of maize farmers in Ghana

Abstract: PurposeThe purpose of this study is to examine the impact of access to credit on technical efficiency (TE) of maize farmers in a developing country, Ghana.Design/methodology/approachThe study employed an instrumental variable approach and the stochastic frontier analysis (SFA) method for the estimation of the results.FindingsThe study found that farmers who have access to agricultural credit stand the chance of increasing TE by a margin of 8%, which also influences the maize production than those who did not h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…These findings confirm why agricultural financing could improve rice farming efficiency, provided that it increases short-term output. This study documented the findings of (Martey et al 2019;Santoso et al 2020;Siaw et al 2020). As per Martey et al (2019), capital loans and farmer organizations promoted both sides.…”
Section: Production Elasticitysupporting
confidence: 63%
See 1 more Smart Citation
“…These findings confirm why agricultural financing could improve rice farming efficiency, provided that it increases short-term output. This study documented the findings of (Martey et al 2019;Santoso et al 2020;Siaw et al 2020). As per Martey et al (2019), capital loans and farmer organizations promoted both sides.…”
Section: Production Elasticitysupporting
confidence: 63%
“…Farmers who participated in farmer groups and farmed on irrigated land were more technically efficient. Since farmer groups serve as a vehicle for enacting policy, farmers were a critical component of rice farming in East Java (Siaw et al 2020). MVP correction for optimal input utilization or percent correction dispersed distribution.…”
Section: Determinants Of Technical Efficiency In Rice Productionmentioning
confidence: 99%
“…Domestic lending to maize farmers should enhance productivity; but, due to high lending rates, most farmers are unable to reap these gains. Farmers who have access to little or moderate agricultural credit, according to Siaw et al ( 2021 ), have an 8% higher probability of boosting technical efficiency, which influences maize output, than those who do not have access to credit. Farmers should create cooperatives to form better partnerships with financial institutions to boost production, and governmental initiatives aimed at expanding smallholder farmers’ access to domestic financing should be pushed aggressively.…”
Section: Resultsmentioning
confidence: 99%
“…10, No. 1 (2020), Lin et al (2019), andSiaw et al (2021). The authors found a significant and positive relationship between credit and productivity.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 93%